Pengaruh Kualitas Pelayanan terhadap Loyalitas yang dimediasi Kepuasan Peserta Pelatihan pada Badan Pendidikan dan Pelatihan DIY - Wajiyono, Wajiyono; Astuti, Widhy Tri; Wisnalmawati, Wisnalmawati (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to analyze the influence of Service Quality on the Loyalty and Satisfaction of trainees at the Yogyakarta Special Region Education and Training Agency (DIY), as well as the influence of Satisfaction on trainee Loyalty, and the influence of Service Quality on Loyalty through participant Satisfaction. This research uses an explanatory method with a survey, conducted in March 2024. The sample taken was 160 respondents. The data collection technique uses a questionnaire, and data analysis uses Partial Least Square (PLS), in accordance with the opinion of Sekaran (2015). The research results show that Service Quality has a significant effect on Loyalty and Satisfaction of training participants, Satisfaction has a significant effect on Loyalty, and Service Quality has a significant effect on Loyalty through Satisfaction of training participants at the DIY Education and Training Agency.